Combining parasite lactate dehydrogenase-based and histidine-rich protein 2-based rapid tests to improve specificity for diagnosis of malaria due to plasmodium knowlesi and other plasmodium species in Sabah, Malaysia - Grigg, Matthew J. (2015)
Plasmodium knowlesi causes severe and fatal malaria in Malaysia. Microscopic misdiagnosis is common and may delay appropriate treatment. P. knowlesi can cross-react with “species-specific” parasite lactate dehydrogenase (pLDH) monoclonal antibodies used in rapid diagnostic tests (RDTs) to detect P. falciparum and P. vivax. At one tertiary-care hospital and two district hospitals in Sabah, we prospectively evaluated two combination RDTs for malaria diagnosis by using both a pan-Plasmodium-pLDH (pan-pLDH)/P. falciparum-specific-pLDH (Pf-pLDH) RDT (OptiMAL-IT) and a non-P. falciparum VOM-pLDH/Pf-HRP2 RDT (CareStart). Differential cross-reactivity among these combinations was hypothesized to differentiate P. knowlesi from other Plasmodium monoinfections. Among 323 patients with PCR-confirmed P. knowlesi (n = 193), P. falciparum (n = 93), and P. vivax (n = 37) monoinfections, the VOM-pLDH individual component had the highest sensitivity for nonsevere (35%; 95% confidence interval [CI], 27 to 43%) and severe (92%; CI, 81 to 100%) P. knowlesi malaria. CareStart demonstrated a P. knowlesi sensitivity of 42% (CI, 34 to 49%) and specificity of 74% (CI, 65 to 82%), a P. vivax sensitivity of 83% (CI, 66 to 93%) and specificity of 71% (CI, 65 to 76%), and a P. falciparum sensitivity of 97% (CI, 90 to 99%) and specificity of 99% (CI, 97 to 100%). OptiMAL-IT demonstrated a P. knowlesi sensitivity of 32% (CI, 25 to 39%) and specificity of 21% (CI, 15 to 29%), a P. vivax sensitivity of 60% (CI, 42 to 75%) and specificity of 97% (CI, 94 to 99%), and a P. falciparum sensitivity of 82% (CI, 72 to 89%) and specificity of 39% (CI, 33 to 46%). The combination of CareStart plus OptiMAL-IT for P. knowlesi using predefined criteria gave a sensitivity of 25% (CI, 19 to 32%) and specificity of 97% (CI, 92 to 99%). Combining two RDT combinations was highly specific for P. knowlesi malaria diagnosis; however, sensitivity was poor. The specificity of pLDH RDTs was decreased for P. vivax and P. falciparum because of P. knowlesi cross-reactivity and cautions against their use alone in areas where P. knowlesi malaria is endemic. Sensitive P. knowlesi-specific RDTs and/or alternative molecular diagnostic tools are needed in areas where P. knowlesi malaria is endemic.